Biochar, Compost, and Biochar–Compost Blend Applications Modulate Growth, Photosynthesis, Osmolytes, and Antioxidant System of Medicinal Plant Alpinia zerumbet - Zulfiqar, Faisal; Chen, Jianjun; Younis, Adnan; Abideen, Zainul; Naveed, Muhammad; Koyro, Hans-Werner; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2021)
Alpinia zerumbet (Zingiberaceae) is a unique ornamental and medicinal plant primarily used in food ingredients and traditional medicine. While organic amendments such as biochar and compost have been demonstrated to improve plant productivity, no studies have examined their effects on the growth, physiology, and secondary metabolites of A. zerumbet. This study evaluated the impact of amendment of biochar (BC), compost (Co), or a mixture (BC+Co) on modifying and improving the growth, photosynthesis, antioxidant status, and secondary metabolism of A. zerumbet grown on sandy loam soil. The morpho-physiological and biochemical investigation revealed variation in the response of A. zerumbet to organic amendments. The amendment of BC and BC + Co significantly increased net photosynthetic rates of plants by more than 28%, chlorophyll a and b contents by 92% and 78%, respectively, and carboxylation efficiency by 50% compared to those grown in the sandy loam soil without amendment. Furthermore, the amendment significantly decreased plant oxidative stress, measured as leaf free-proline and glycine betaine. Enzymatic antioxidant activity, total phenols, and flavonoids also varied in their response to the organic amendments. In conclusion, this study shows that biochar and/or compost amendments are an efficient and sustainable method for improving the metabolite contents and reducing oxidative stress in A. zerumbet.